Shakespeare on the American Yiddish stage - Berkowitz, Joel, 1965- (Studies in theatre history and culture., 2002)
The professional Yiddish theatre started in 1876 in Eastern Europe; with the assassination of Tsar Alexander II in 1881, masses of Eastern European Jews began moving westward, and New York--Manhattan's Bowery and Second Avenue--soon became the world's center of Yiddish theatre. At first the Yiddish repertoire revolved around comedies, operettas, and melodramas, but by the early 1890s America's Yiddish actors were wild about Shakespeare. In Shakespeare on the American Yiddish Stage, Joel Berkowitz knowledgably and intelligently constructs the history of this unique theatrical culture.